Padrão de distribuição espacial do carbono arbóreo-arbustivo em duas áreas de savana em Roraima - Cunha, Mariana Souza da (2010)
Tree and schrubs represent the vegetation in savanna areas with higher biomass. Spatial distribution and quantification are fundamental to quantify carbon stock in open areas in Amazonia. The objective of this study was to determine the distribution pattern of carbon/biomass of species of trees and schrubs in two savanna areas in the municipality Boa Vista (Roraima), Água Boa (AB) and Monte Cristo (MC), according to the soil’s chemical and physical characteristics. Methodology consisted in a phytosociological survey in permanent plots established in the two areas, thus estimating the biomass and carbon stock of the tree and schrub specimens by indirect method. The main results suggest low richness and diversity of species to AB (S=4; H’=0.27) and MC (S=7; H’=0.74), but with medium similarity (54.5%). Byrsonima crassifolia (L.) H.B.K. (AB=61.98%) and Curatella americana L. (MC=37.63%) were the species with high importance value index (IVI). The aboveground carbon/biomass stock for this group of plants was higher on the mosaic environments (Sg+Sp) for AB (1034.74 kg C/ha) and MC (1275.16 kg C/ha), followed by grassland (Sg) typologies represented for “campo sujo” and “campo limpo” savannas of the two areas. Ordination biomass/carbon stocks according to the different plots formed typical groupings of the different savannas typologies. The effect of edaphic variables on carbon stocks were registered by ordination, suggesting specific patterns of spatial distribution for the different groups of species in each area. However, some species did not register the same pattern of spatial distribution in both grids, thus suggesting that different types of soil which has the same phytophisionomy, not necessarily concentrate the same carbon stock derived of the same species.